2023
DOI: 10.1007/s10577-023-09717-9
|View full text |Cite
|
Sign up to set email alerts
|

X-chromosome inactivation patterns depend on age and tissue but not conception method in humans

Abstract: Female somatic X-chromosome inactivation (XCI) balances the X-linked transcriptional dosages between the sexes, randomly silencing the maternal or paternal X chromosome in each cell of 46,XX females. Skewed XCI toward one parental X has been observed in association with ageing and in some female carriers of X-linked diseases. To address the problem of non-random XCI, we quantified the XCI skew in different biological samples of naturally conceived females of different age groups and girls conceived after in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…With lower coverage, the two groups may not be sufficiently sampled and cluster definition becomes more difficult. It is important to note that skew can vary from tissue to tissue within one individual [4], and certain tissues become more clonal/skewed with age [32, 33]. Therefore there is a risk in extrapolating to a different, inaccessible, disease-relevant tissue.…”
Section: Discussionmentioning
confidence: 99%
“…With lower coverage, the two groups may not be sufficiently sampled and cluster definition becomes more difficult. It is important to note that skew can vary from tissue to tissue within one individual [4], and certain tissues become more clonal/skewed with age [32, 33]. Therefore there is a risk in extrapolating to a different, inaccessible, disease-relevant tissue.…”
Section: Discussionmentioning
confidence: 99%
“…This observation strengthened the notion that analysis of XCI patterns in peripheral leukocytes is insufficient. The XCI pattern may differ in different tissues and vary over time (Juchniewicz et al, 2023; Wong et al, 2011). For example, Juchniewicz et al (2023) reported that XCI skew differed between saliva, blood, and buccal swabs in females.…”
Section: Discussionmentioning
confidence: 99%
“…The XCI pattern may differ in different tissues and vary over time (Juchniewicz et al, 2023; Wong et al, 2011). For example, Juchniewicz et al (2023) reported that XCI skew differed between saliva, blood, and buccal swabs in females. Other mechanisms, such as environmental factors and DNA methylation, may also be involved.…”
Section: Discussionmentioning
confidence: 99%